Integration And Implementation Of Character Education In History Learning At SMA Negeri 15, Kepulauan Tanimbar Regency During The Covid-19 Pandemic - Luturmas, Rianko; Djono, Djono; Rejekiningsih, Triana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This study aims to describe how urgent character education is and how teachers implement it in history learning at SMA Negeri 15, Kepulauan Tanimbar Regency, which is related to three aspects of learning, namely planning, implementation (learning strategies and methods), and evaluation during the Covid-19 pandemic.(19) This study used qualitative research method. It was conducted in the odd semester of the 2021–2022 academic year at SMA Negeri 15, Kepulauan Tanimbar Regency, Maluku Province. There were two sources of data, primary and secondary data. It was found that globalization and modernization have a negative impact on students' morals and associations, and character education in history learning is important during the Covid-19 pandemic so that students can learn from history. In learning implementation, history teachers make lesson plans adapted from the syllabus from the government. In the implementation of history learning during this pandemic, teachers must maximize learning strategies and methods, especially in utilizing media and historical learning resources. Learning evaluation should be carried out from scratch to examine the success of the implementation of character education in history learning during this pandemic. Teachers can evaluate history learning by group tests or individual tests to find out the changes in students' affective learning outcomes.